Pemberdayaan Kader PKK Melalui Pelatihan Produksi Lilin Aromaterapi dalam Pemanfaatan Minyak Jelantah di Desa Babakan, Pangandaran - Jenal Abidin; Nurina Fadilatu Shaumi; Ia Rahmawati; Diah Nurlatipah; Devi Sri Rahayu; Aziz, Nur; Erni Triana Agustin; Ariz Salma Hernanda; Ahmad Fauzi; Nadia Lutfi Magpiroh; Dede Mulyana; Annisa Nurahmayanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat UIN Prof. K.H. Saifuddin Zuhri, 2025)
This Community Service Program aims to provide outreach and training on making aromatherapy candles from used cooking oil to women PKK cadres in Babakan Village, as an effort to reduce used cooking oil waste while increasing environmental awareness. The method used in this service uses the Participatory Action Research (PAR) method, a research approach that prioritizes the active involvement of participants in every stage of the research process, from planning to implementation and evaluation. Based on the identification of problems and potential uses of used cooking oil, education is provided in the form of empowerment about training on the benefits of using used cooking oil and its environmentally friendly management. Demonstrations are carried out to introduce aromatherapy candle making techniques. The results of the training show an increase in the knowledge and skills of women PKK cadres in processing used cooking oil waste into economically valuable products, furthermore, this activity has also succeeded in having a positive impact in reducing environmental pollution and opening new business opportunities for the community that can be used as a model for sustainable waste management in other areas